Innovation effects of science-related technological opportunities: Theoretical considerations and empirical findings for firms in the German manufacturing industry - Wolfgang Becker; Jürgen Peters (Universität Augsburg, Institut für Volkswirtschaftslehre, 2002)
This paper investigates the innovation effects of science-related technological opportunities. Against the background of theoretical considerations about the interrelation of innovation and the adaptation of external (knowledge) resources, the impacts of technological opportunities stemming from scientific institutions on firms' innovation input and output are empirically analyzed for the German manufacturing industry. The investigations focus on the question whether science-related technological opportunities are used as complements or substitutes in the innovation process. The estimations indicate complementary relationships between firms' innovation input and technological opportunities stemming from scientific institutions. The adaptation of science-related knowledge resources has stimulating effects on the intensity of inhouse R&D. The results for the innovation output effects are ambiguous. On the one hand, empirical evidence for complementary impacts on the realisation of improved products could be found. On the other hand, science-related technological opportunities have no enhancing effects on the probability of realizing new products. Obviously, knowledge from universities and research institutes stimulates the development of new products more indirectly by increasing inhouse capacities and enhancing R&D efficiency.
urn:nbn:de:bvb:384-opus4-712326
Keywords: O31; I20; L20; L60; 330; innovation activities; technological opportunities; scientific institutions; manufacturing industry